The sensitivity and specificity of pulmonary carbon dioxide elimination for noninvasive assessment of fluid responsiveness - Tusman, Gerardo (2016)
BACKGROUND: We sought to determine whether the response of pulmonary elimination of CO2 (Vco2) to a sudden increase in positive end-expiratory pressure (PEEP) could predict fluid responsiveness and serve as a noninvasive surrogate for cardiac index (CI).METHODS: Fifty-two patients undergoing cardiovascular surgery were included in this study. By using a constant-flow ventilation mode, we performed a PEEP challenge of 1-minute increase in PEEP from 5 to 10 cm H2O. At PEEP of 5 cm H2O, patients were preloaded with 500 mL IV salinesolution after which a second PEEP challenge was performed. Patients in whom fluid administration increased CI by ≥15% from the individual baseline value were defined as volume responders.Beat-by-beat CI was derived from arterial pulse contour analysis, and breath-by-breath Vco2 data were collected during the protocol. The sensitivity and specificity of Vco2 for detecting thefluid responders according to CI was performed by the receiver operating Characteristic curves.RESULTS: Twenty-one of 52 patients were identified as fluid responders (40%). The PEEP maneuver before fluid administration decreased CI from 2.65 ± 0.34 to 2.21 ± 0.32 L/min/m2 (P = 0.0011) and Vco2 from 150 ± 23 to 123 ± 23 mL/min (P = 0.0036) in responders, whereas the changes in CI and Vco2 were not significant in nonresponders. The PEEP challenge afterfluid administration induced no significant changes in CI and Vco2, in neither responders nor nonresponders. PEEP-induced decreases in CI and Vco2 before fluid administration were well correlated (r2 = 0.75, P < 0.0001) but not thereafter. The area under the receiver operating characteristic curves for a PEEP-induced decrease in ΔCI and ΔVco2 was 0.99, with a 95% confidence interval from 0.96 to 0.99 for ΔCI and from 0.97 to 0.99 for ΔVco2. During the PEEP challenge,a decrease in Vco2 by 11% predicted fluid responsiveness with a sensitivity of 0.90 (95% confidence interval, 0.87?0.93) and a specificity of 0.95 (95% confidence interval, 0.92?0.98).CONCLUSIONS: PEEP-induced changes in Vco2 predicted fluid responsiveness with accuracy in patients undergoing cardiac surgery. (Anesth Analg 2016;122:1404?11)